Elevated Levels of Cerebrospinal Fluid and Plasma Interleukin-37 in Patients with Guillain-Barré Syndrome - Cong Li; Pingwei Zhao; Xiguang Sun; Yuanyuan Che; Yanfang Jiang (Mediators of Inflammation)
Aims. Interleukin-37 (IL-37) is an anti-inflammatory cytokine. This study aims to investigate the concentrations of plasma and cerebrospinal fluid (CSF) IL-37 in patients with Guillain-Barré Syndrome (GBS). Methods. The levels of plasma and CSF IL-37, IL-17A, IFN-γ, and TNF-α in 25 GBS patients and 20 healthy controls (HC) were determined by enzyme-linked immunoabsorbent assay and flow cytometric bead array assay, respectively. The values of clinical parameters in the patients were also measured. Results. The concentrations of plasma IL-37, IL-17A, IFN-γ, and TNF-α and CSF IL-37 and IL-17A in patients at the acute phase of GBS were significantly higher than those in the HC. The levels of plasma IL-37, IL-17A, IFN-γ, and TNF-α were positively correlated in those patients, and the levels of CSF IL-37 and IL-17A as well as the levels of plasma TNF-α were correlated positively with the GBS disability scale scores (GDSs) in those patients. Treatment with intravenous immunoglobulin significantly reduced the levels of plasma IL-37, IL-17A, IFN-γ, and TNF-α in the drug-responding patients. Conclusions. Our findings indicate higher levels of plasma and CSF IL-37 and IL-17A and other proinflammatory cytokines in patients with GBS.